A novel method using 18O and metal isobaric labeling combined with multiple reaction monitoring mass spectrometry for the absolute quantification of a target proteome1. Issue 19 (7th October 2015) - Yan, Hui; Hao, Feiran; Li, Nannan; Li, Jiabin; Peng, Bo; Zai, Rui; Zhang, Yangjun; Qian, Xiaohong
<x xml:space="preserve">Abstract</x> A novel method using 18O/metal isobaric labeling combined with multiple reaction monitoring mass spectrometry for absolute quantification of target proteomes was established.